Evaluation Toxicity 0fDigitariasanguinalis andClerodendruminerme to Control Blady grass Imperata cylindrica. - ALhabib, Amaal A.S; Aboud, Anmar S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Laboratory and field experiment were conducted at MustansiryahUniversity in 2010 to investigate the possible allelopathic potential ofDigitariasanguinalis (L.) Large crabgrass andClerodenduminerme on the seed germination and seedling growth of bladygrass (Imperata cylindrica), the results showed areduce of 44%and 43% in seed germinationby leaves extracts ofClerodenduminermeandDigitariasanguinalisrespectively in 50% concentration and 61% and 62% in 100% concentration. Root and shoot length of blady grass seedlings growth were reduced by an average of 75-70%. Field experiments indicated thatcrude material of Clerodenduminerme and Digitariasanguinalisin50 gm/ m2 gave the highest control on blady grass than the herbicide Ground- up in 25ml/liter and 12.5 ml/liter concentration in reduced blady grass density per unit area ,plant length,and foliage dry weight. Phytotox agents were identified assaponin, flavon, glycoside, phenolic, alkaloid, steroid, tannin ,coumarinand essensial oil were detected in leaves extract of Clerodenduminermeand Digitariasanguinalis